Numerical Simulation of Water Transport in Unsaturated Recycled Aggregate Concrete - Liu, Zhaolin; Zhang, Peng; Bao, Jiuwen; Hu, Yu (Frontiers in Materials, 2020)
The old mortar attached to recycled aggregate (RA) is the main reason for the difference in water movement between recycled aggregate concrete (RAC) and natural aggregate concrete (NAC). In this study, considering the old and new interfacial transition zones (ITZs), a five-phase composite model for describing the water transport and distribution in RAC is established at the mesoscale. The key parameters describing water unsaturated transport in two types of mortar, saturated hydraulic conductivity (Ks) and van Genuchten model parameters (α, n), are obtained through the constant-head permeability test and isothermal adsorption test. By using the finite element method, the numerical simulations of unsaturated moisture movement in the homogeneous mortar, NAC, and five-phase RAC are systematically carried out. The proposed moisture transport model in the matrix is validated by comparison with the available experimental findings from the literature. The results show that the model can well predict unsaturated water transport in cement-based materials, including RAC. A parameter sensitivity analysis is undertaken to ascertain the main influencing factors of water transport in RAC. It is concluded that the RA replacement rate (Rra), the thickness of the old mortar (dm), and the aggregate volume fraction (Fa) are the primary parameters affecting moisture movement in RAC.